Academic Burnout in View of Gender in Post-Pandemic Padang State University Students - Nadya Nanda Dwi Putri; Maya Yasmin (Universitas Muhammadiyah Banjarmasin, 2023)
Academic Burnout is boredom because you are too involved in academic or learning activities. Low student learning outcomes can be caused by high levels of academic saturation. This research at Padang State University aims to try to describe differences in academic saturation between male and female students at Padang State University after the pandemic. 385 post-pandemic Padang State University students became the research sample. Student batches of 2021, 2020 and 2019 were taken as samples using proportional stratified sampling, which is the method used when the members or elements of the population are not homogeneous and are stratified proportionally. Quantitative method with comparative design is the type of research used. School Burnout Inventory (SBI) is an academic burnout scale instrument that is used to collect data with the validity of each item being greater than 0.50 and a reliable value of 0.881. With the help of SPSS software version 22.0 for Windows using the independent sample t-test method. The results of the analysis show that the academic saturation of male and female students is significantly different. The findings of this study also show that female students at Padang State University are more likely to experience post-pandemic academic burnout than male students. The findings of this study can also be used by campuses to develop learning strategies that will reduce students academic saturation levels.